(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The study examined the influence of the personal characteristics of extension agents in Edo State Agricultural Development Programme (ESADP) on their job performance. A well - structured questionnaire was used to collect information from fifty-three respondents, spread across the ADP blocks in the three agricultural zones in the study area. Data were analyzed using descriptive statistics and chi-square. The findings of the study showed that majority of the respondents were male (66.0%) and married (94.3%). Majority (83%) had OND/NCE certificate and were relatively young (average age = 40 years) and experienced as extension agents (average = 14 years). The job performance of majority of the extension workers was rated high (58.5%). Also, Chi- square result showed that there was no significant association between the personal characteristics of the extension agents and their job performance. The study therefore suggests the need to examine organizational factors as crucial incentives needed to enhance the job performance of the workers in the study area